156k views
5 votes
Y = 4x – 18
y = -5x +9

User Jeff Sharp
by
4.9k points

2 Answers

4 votes

Answer:

x=3

y = -6

Explanation:

y = 4x – 18

y = -5x +9

Set the two equations equal

4x – 18 = -5x +9

Add 5x to each side

4x – 18 +5x= -5x+5x +9

9x -18 = 9

Add 18 to each side

9x -18 +18 = 9+18

9x =27

Divide by 8

9x/9 = 27/9

x = 3

Now find y

y = 4x-18

y = 4*3 -18

y =12-18

y = -6

User Kevin Van Ryckegem
by
4.7k points
4 votes

Answer:

(3, -6)

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

  1. Brackets
  2. Parenthesis
  3. Exponents
  4. Multiplication
  5. Division
  6. Addition
  7. Subtraction
  • Left to Right

Equality Properties

  • Multiplication Property of Equality
  • Division Property of Equality
  • Addition Property of Equality
  • Subtraction Property of Equality

Algebra I

  • Coordinates (x, y)
  • Terms/Coefficients
  • Solving systems of equations using substitution/elimination

Explanation:

Step 1: Define Systems

y = 4x - 18

y = -5x + 9

Step 2: Solve for x

Substitution

  1. Substitute in y [2nd Equation]: 4x - 18 = -5x + 9
  2. [Addition Property of Equality] Add 5x on both sides: 9x - 18 = 9
  3. [Addition Property of Equality] Add 18 on both sides: 9x = 27
  4. [Division Property of Equality] Divide 9 on both sides: x = 3

Step 3: Solve for y

  1. Substitute in x [1st Equation]: y = 4(3) - 18
  2. Multiply: y = 12 - 18
  3. Subtract: y = -6
User Sdcbr
by
4.4k points